UPAYA MENINGKATKAN HASIL BELAJAR PASSING DALAM PERMAINAN SEPAK BOLA DENGAN MENERAPKAN GAYA MENGAJAR RESIPROKAL PADA SISWA KELAS VIII-4 SMP KARYA CIPTA MEDAN T.A. 2017/2018 - Dharma Andarsum N (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
The purpose of this study was to determine the learning outcomes of passing in soccer games by applying a reciprocal teaching style to students of class VIII-4 SMP Karya Cipta Medan T.A. 2017/2018. This research method is Classroom Action Research and the subjects in this class action research are class VIII-4, which consists of 34 students. Consisting of 20 daughters and 14 sons. The analysis of the results of learning passing in the student's football game on the first test of the first cycle turned out to be better than the initial test although the results were not maximal enough, so it was necessary to proceed to the implementation of the second cycle. In the first cycle the teacher found the difficulties experienced by students and teachers in learning.